Dinamika Lafal Mawlā dalam Al-Qur’an: Analisis Kajian Semantik Ferdinand De Saussure - Mohammad Nabil Iklil Mubarok; Moh. Zahid (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study traces the development of the meaning of the term mawlā from the pre-Qur'anic to the post-Qur'anic period, focusing on the diversity of meanings that appear in the texts of the Qur'an. As a key term in the Qur'an, mawlā has a broad range of meanings, from the vertical relationship between humans and God to the horizontal relationship between humans. This study aims to examine the dynamics of these meanings through an analysis of a number of Qur'anic verses, including Al-Taḥrīm (66:2), Al-Ḥajj (22:13), and others. Using a qualitative approach and descriptive-analytical methods, this study utilizes Ferdinand de Saussure's synchronic and diachronic theories as a semantic analysis framework. Secondary data comes from various classical to modern interpretations, Arabic dictionaries, and pre-Islamic literary works. The results show that the meaning of mawlā is contextual, functional, and not static. Synchronically, this term refers to various roles such as helper, protector, or regulator in the context of vertical and horizontal relationships. Diachronically, there has been a shift in meaning from the terms patronage and slavery in the Jahiliyyah period to spiritual and egalitarian concepts in Islam, to becoming a religious title in the post-Qur'anic tradition. These findings confirm that the meaning of mawlā is differential, depending on the system and context, rather than having a fixed or singular meaning.